Relationship between cortical and medullary thickness and glomerular filtration rate among living kidney donors. Issue 3 (15th March 2023) - Kuhnel, Lukas; Vu, Thomas; Wood, Simon T.; Francis, Ross S.; Trnka, Peter; Ellis, Robert J.
Abstract: The relationship between the kidney cortex and medulla is not well understood in healthy populations. This study characterised the relationship between cortical/medullary thickness and measured glomerular filtration rate (GFR) in 390 living kidney donors. A positive relationship was observed between medullary, but not cortical, thickness and GFR. We propose that this reflects a correlation between juxtamedullary nephron number and GFR.